(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
The spiritual heritage of the peoples of Uzbekistan possesses a great history and rich scientific-traditional foundations. This article analyzes the development of Sufi scientific heritage in Central Asia during the Timurid era and subsequent centuries, focusing especially on the activities and scholarly works of the Naqshbandiya-Mujaddidiya tariqa. Information is also provided on the Sufi teachings of prominent thinkers such as Sheikh Khudoydod and Musokhon Dahbedi and their works. The article emphasizes the importance of studying historical sources, tafsirs, and scientific heritage. This research serves as a basis for broader investigation into the legacy of Uzbek and Central Asian scholars.